Anti-bacterial Properties of Melatonin against Mycobacterium Tuberculosis in Vitro - M. Jasim, Thamer; G.Alabbassi, Mustafa; F. Hatem Almuqdadi, Suhad; K. Kamel, Jinan (Iraqi Journal of Pharmaceutical Sciences, 2017)
57 isolates of Mycobacterium tuberculosis and Mycobacterium bovis were identified; they were isolated from different clinical sources which included sputum, bronchial wash, abscess, pleural fluid, gastric fluid, eye fluid, and CSF, also urine and ear swab. This investigation was carried out on 198 patient attended National Reference Laboratory for T.B during September 2009. Also the study declared that the ratio of separation of this bacterium from male was (67.6%) and it’s higher than the ratio of separation this bacterium from females which was (32.3%). The susceptibility of Mycobacterium tuberculosis to melatonin was evaluated. Many concentrations of melatonin were prepared to investigate it as antibacterial drug against multidrug resistant Mycobacterium tuberculosis and Mycobacterium bovis. Suspension bacteria (10-1, 10-3 and 10-5) were cultured on Lowenstein-Jensen media (LJ) contains melatonin, while control media without this drug. Six isolates were chosen according to their susceptibility patterns; they were resisting to Rifampicin, Streptomycin, Isonicotinic –hydrazide and sensitive to Ethambutol. In conclusion, these in vitro studies clearly demonstrate anti-bacterial effects of melatonin. Among possible mechanisms, it is concluded that melatonin showed antibacterial effects against multidrug resistant T.B by reducing intracellular substrates. Identifying the mode of action could be of great help in developing and researching new anti-bacterial drugs.Key words: Antibacterial, Melatonin, Mycobacterium tuberculosis